PENGGUNAAN MEDIA GAMBAR HEWAN UNTUK MENINGKATKAN KEMAMPUAN MENULIS PADA ANAK USIA DINI (Penelitian Tindakan Kelas Terhadap Peserta Didik di Kelompok B1 di TK Karya Kencana di Gunungkencana Kab. Lebak Banten Tahun Ajaran 2020/2021) - Bernawati, - (2021)
This research is entitled "Use of Animal Picture Media to Improve Writing Ability in Early Childhood (Classroom Action Research on Students in Group B1 Kindergarten Karya Kencana Academic Year 2021/2021)". Early childhood is children aged 0-6 years and can This is called the golden age as well as a critical period for children in life. As a critical period and an important period, all the potential possessed by children is aimed at developing. One aspect of the basic skills that need to be developed in kindergarten or early childhood education is the development of basic language skills in terms of writing. Writing ability is a language skill that is used to communicate indirectly, not face to face with other people. Writing is a productive and expressive activity. The writing ability of children at Karya Kencana Kindergarten in Gunungkencana Kab. Lebak-Banten average is not optimal. This can be seen when the teacher gives assignments by doing writing activities, there are still children who are not able and have difficulty and are also still found writing inverted letters. So the goal to be achieved in this study is to prove whether through the media of animal images with activities to thicken letters, imitate letter shapes and arrange letters into one word can improve writing skills in early childhood in the B1 group of Kindergarten Karya Kencana. This research is in the form of classroom action research (CAR) on 15 students of group B1 TK Karya Kencana. Conducted through two cycles, each cycle consisting of two meetings each meeting consists of four stages, namely planning, implementation, observation and reflection. The results of the study were analyzed using a descriptive method with a qualitative approach, and the results showed a significant increase. This is evidenced by an increase in the first cycle with a total range of 53% with the criteria of Developing According to Expectations (BSH), then an increase of 80% in the second cycle with the criteria of Very Good Development (BSB). During the implementation of classroom action research, researchers got findings that can be used as references and recommends, namely at the beginning of learning activities the teacher must motivate children so that children are able to complete their tasks well in innovating and more creative learning media. Keywords:Children's Writing Ability, Animal Picture Media